The Impact of China's "Stadium Diplomacy" on Local Economic Development in Sub-Saharan Africa - Lindlacher Valentin; Gustav Pirich (Center for Economic Studies and ifo Institute (CESifo), 2024)
This study investigates the economic impact of China's "stadium diplomacy" in Sub-Saharan Africa. Exploiting the staggered timing of the construction in a difference-in-differences framework, we analyze the effect of Chinese-built and financed stadiums on local economic development. Employing nighttime light satellite data, we provide both an aggregate and spatially disaggregated assessment of these investments. We find that a stadium's city nighttime light intensity increases by 25 percent, on average, after stadium completion. The stadium's direct surrounding increases by 34 percent, on average, in its nighttime light activity. The effects can be attributed to the stadiums but are not only visible close to the stadium's location. The effect remains strong when controlling for other local Chinese investments. Thus, we find evidence for beneficial effects of Chinese-built and financed stadiums on local economic development in Sub-Saharan Africa, contrasting with the widely held notion that China's development finance projects constitute "white elephants".
Keywords: O18; R11; O55; R53; Z20; 330; stadium diplomacy; regional development; nighttime light; local public infrastructure; Sub-Saharan Africa